Analysis of the effect of Supplementary Food Provision (PMT) budget distribution on improving child nutrition for stunting eradication in Mimika Regency - Naa, Oktovina; Umar, Hasan Basri; Ngutra, Risky Novan (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the effect of the distribution of the Supplementary Food Provision (PMT) budget on improving child nutrition as part of stunting alleviation efforts in Mimika Regency. The focus is on how government allocations and budget management contribute to nutritional improvements among vulnerable groups. Research methodology: The research applies an associative method to identify the relationship between budget distribution and nutritional outcomes. Data were collected through structured questionnaires and in-depth interviews with respondents directly involved in program implementation. The analysis technique used is simple linear regression to measure the effect of PMT budget allocation on child nutrition indicators. Results: Findings indicate that the distribution of the PMT budget has brought tangible benefits, particularly to children under five and pregnant women at risk of malnutrition. The regression results confirm that budget allocation has a positive and statistically significant impact on improving child nutrition for stunting alleviation in Mimika Regency. Nevertheless, the program still faces obstacles, including uneven distribution, limited monitoring, and external socioeconomic factors. Addressing these barriers is essential for achieving optimal and sustainable results. Conclusions: The distribution of the PMT budget plays a crucial role in enhancing children’s nutritional status and supporting stunting reduction strategies. Proper targeting and effective use of the budget can strengthen outcomes, though improvements in governance, monitoring, and community engagement remain necessary. Limitations: The study is limited by reliance on local government reports, a narrow geographic scope, and the exclusion of external determinants such as parenting practices, healthcare access, and socioeconomic conditions. Contribution: This study provides practical insights for policymakers to refine budget management and intervention strategies, while academically contributing to the literature on the role of public funding in combating malnutrition and stunting.